Building Resilient Human Service Organizations. Issue 1 (1st January 2016) - van Breda, Adrian D.
Abstract : Human service organizations aim to provide high quality and relevant social services to their clients. During times of adversity, such organizations require additional strengths and assets to sustain such services and to ensure the well-being of the organization and its staff. Organizational resilience is an important but underresearched approach to building the capacity of human service organizations. This paper presents a three-legged conceptual model of organizational resilience, based on empirical research and theory, comprising system, staff, and service models. The paper gives some attention to practice implications for managers and supervisors of human service organizations.